2018
DOI: 10.1002/anie.201800361
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Synthesis of Z‐Olefins through Rh‐Catalyzed Formate‐Mediated 1,6‐Reduction

Abstract: Z-olefins are important functional units in synthetic chemistry; their preparation has thus received considerable attention. Many prevailing methods for cis-olefination are complicated by the presence of multiple unsaturated units or electrophilic functional groups. In this study, Z-olefins are delivered through selective reduction of activated dienes using formic acid. The reaction proceeds with high regio- and stereoselectivity (typically >90:10 and >95:5, respectively) and preserves other alkenyl, alkynyl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…[7] Thelack of generality in Z-selective diene additions highlights the difficulty in controlling both site-and stereoselectivity in catalytic diene functionalization, [8] particularly in those reactions that generate thermodynamically less favorable product isomers. [9] From am echanistic perspective,i mproving reductive chemoselectivity while inhibiting chain-walking events in diene-aldehyde coupling can potentially be realized by tailoring the reactivity of the Rh intermediates involved in the reaction pathway.Specifically,ifboth diene insertion into the Rh-hydride catalyst and electrophilic capture of the resultant Rh-allyl outpace undesirable isomerization, bhydride elimination, or other reductive processes,adirect and selective coupling process should be possible.Werecently reported that formic acid acts as reducing agent for the Zselective 1,6-reduction of dienyl esters [10] and questioned whether this pathway could be diverted to enable reductive coupling.F ormic acid has been used as areductant for metalcatalyzed CÀCb ond-forming carbonyl allylation and vinylation processes. [11] In this report, we demonstrate that mixtures of Rh precatalysts,1 ,5-cyclooctadiene (COD), and PPh 3 mediate the isomerization-free,stereoselective addition of diene-derived nucleophiles to aldehydes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Thelack of generality in Z-selective diene additions highlights the difficulty in controlling both site-and stereoselectivity in catalytic diene functionalization, [8] particularly in those reactions that generate thermodynamically less favorable product isomers. [9] From am echanistic perspective,i mproving reductive chemoselectivity while inhibiting chain-walking events in diene-aldehyde coupling can potentially be realized by tailoring the reactivity of the Rh intermediates involved in the reaction pathway.Specifically,ifboth diene insertion into the Rh-hydride catalyst and electrophilic capture of the resultant Rh-allyl outpace undesirable isomerization, bhydride elimination, or other reductive processes,adirect and selective coupling process should be possible.Werecently reported that formic acid acts as reducing agent for the Zselective 1,6-reduction of dienyl esters [10] and questioned whether this pathway could be diverted to enable reductive coupling.F ormic acid has been used as areductant for metalcatalyzed CÀCb ond-forming carbonyl allylation and vinylation processes. [11] In this report, we demonstrate that mixtures of Rh precatalysts,1 ,5-cyclooctadiene (COD), and PPh 3 mediate the isomerization-free,stereoselective addition of diene-derived nucleophiles to aldehydes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, if both diene insertion into the Rh‐hydride catalyst and electrophilic capture of the resultant Rh‐allyl outpace undesirable isomerization, β‐hydride elimination, or other reductive processes, a direct and selective coupling process should be possible. We recently reported that formic acid acts as reducing agent for the Z ‐selective 1,6‐reduction of dienyl esters and questioned whether this pathway could be diverted to enable reductive coupling. Formic acid has been used as a reductant for metal‐catalyzed C−C bond‐forming carbonyl allylation and vinylation processes .…”
Section: Introductionmentioning
confidence: 99%
“…First, the reaction of [Rh(cod)OH] 2 with Et 3 B generates the ethylrhodium species 3 , which undergoes β‐hydride elimination to give rhodium hydride 4 . Hydrorhodation of 1,3‐diene 1 a with 4 then provides allylrhodium species 5A , which undergoes σ‐π‐σ isomerization to give 5B . β‐Hydride elimination of 5B gives a rhodium hydride coordinated to benzyl sorbate (as in 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…The initial experiments were conducted with N ‐phenyl α‐diazo‐γ‐butyrolactam ( 1a ) and p ‐toluidine ( 2a ) (Table ). With Rh 2 (OAc) 4 , employed as the catalyst, 50 % of the desired product ( 3a ) was observed by 1 H NMR analysis of the crude mixture (entry 1). With more reactive Rh 2 (esp) 2 , employed in 5 mol‐% quantity (entry 2), the NH‐insertion product 3a NMR yield was raised to 62 % and remained virtually identical when the catalyst amount was reduced 10‐fold (entry 3).…”
Section: Resultsmentioning
confidence: 99%